Current trends in the treatments of choledochal cysts in pediatric patients in Korea in the era of minimally invasive surgery: narrative review - Ayoung Kang; Soo-Hong Kim; Hae-Young Kim (Journal of Medicine and Life Science)
Choledochal cyst (CC) is a rare biliary tract disease characterized by cystic dilation of the biliary duct that requires surgical resection because of its malignant potential and associated complications. Minimally invasive surgeries (MIS), such as laparoscopy and robotics, have been increasingly used for the treatment of CC. This study investigated the current treatment trends and outcomes of pediatric CC in Korea, with a focus on MIS. We reviewed papers and conference abstracts on pediatric CC in Korea, published between 2000 and 2024. The incidence of CC in Korea is similar to that in Japan, with a rate of 1 in 13,000 individuals and a male-to-female ratio of 1:3 to 1:4. Type I CC was the most common (73.8%), followed by type IVA (16.0%). The first pediatric laparoscopy for CC in Korea was performed in 2006, and the first robotic surgery was in 2011. According to national surveys conducted by the Korean Association of Pediatric Surgeons in 2002 and 2017, all surgeries performed in the 2000s were open procedures. By the late 2010s, 54.3% of surgeries had been performed using MIS (laparoscopy, 31.1%; robotic surgery, 23.2%). Although few institutions have reported MIS outcomes for CC in Korea, laparoscopic surgery has been shown to be safe and cosmetically favorable. The surgical outcomes of robotic surgery are similar, but with challenges such as longer operation times, difficulties in small patients, and higher costs. Although laparoscopic surgery is currently the standard treatment in Korea, robotic surgery may become another standard procedure if the technological limitations can be overcome.